Industrial Ownership and Environmental Performance : Evidence from China - Wang, Hua; Jin, Yanhong (World Bank, Washington, DC, 2014)
The authors explore the differences in pollution control performance of industries with different types of ownership in China-state-owned (SOE), collectively- or community-owned (COE), privately owned (POE), companies with foreign direct investment (FDI), and joint ventures. About 1,000 industrial firms in three provinces of China were surveyed, and detailed 1999 firm-level information was obtained. The authors analyzed the differences between firms in receiving and reacting to environmental regulatory enforcement, community pressure, environmental services, as well as in the firm's internal environmental management among the different types of ownership. The authors also conducted econometric analyses on the determinants of pollution discharge performance. The results show that foreign direct investment and collectively-owned enterprises have better environmental performances in terms of water pollution discharge intensity, while state-owned enterprises and privately owned enterprises in China are the worst performers. The results also suggest that collectively-owned enterprises in China do internalize environmental externalities.